Strategies for Enhancing the Organizational Commitment of Faculty Members at Iran University of Medical Sciences - Ali Kabir; Salime Goharinezhad; Mehrnoosh Inanlou; Leili Borimnejad (نشریه پرستاری ایران)
Background & Aims Organizational commitment includes behaviors that lead employees to strive to achieve the organization’s goals and stay loyal to the organization and its values. This study aimed to provide recommendations for improving the organizational commitment of the faculty members of Iran University of Medical Sciences (IUMS), Tehran, Iran. Materials & Methods The present study used the triangulation approach conducted at the IUMS from the summer of 2020 to June 2023. In the first phase, Allen and Meyer (2004)’s revised version of the organizational commitment scale (OCS) was completed by the faculty members of the IUMS. Descriptive statistics and analysis of variance were used to analyze the collected data. In the second phase, 15 purposefully selected faculty members participated in interviews, ensuring their maximum diversity. Graneheim and Lundman’s qualitative content analysis was used. The findings were finally presented to the faculty members, and they prioritized the practical recommendations. Results The OCS scores were in a range of 74-124 (Mean=99.86), indicating that the organizational commitment of the faculty members was above average. The mean scores for the OCS dimensions of affective, continuance, and normative were 4.39, 4.05, and 4.09, respectively, indicating that the highest score belonged to the affective commitment. The effective factors were categorized as individual, organizational, and extra-organizational factors. The most important proposed solutions were: Developing meritocracy criteria for key positions of the university, modifying the appointments and dismissals, supervising and monitoring the performance of the managers of the faculties and research centers in the fair distribution of resources, and law violations. Conclusion Meritocracy is the most important factor for improving the organizational commitment of the IUMS faculty members. Therefore, it is recommended that meritocracy criteria be developed to make appointments and dismissals more objective, reduce discrimination, and increase the organizational commitment of faculty members.